Pengaruh Ukuran Perusahaan, Leverage, dan Kepemilikan Manajerial Terhadap Manajemen Laba (Studi pada Perusahaan Manufaktur Sub Sektor Makanan dan Minuman yang Terdaftar di BEI Periode 2018 - 2022) - Wirda Nurmatun Putri; Mira Nurhikmat; Suhroji Adha (Trending: Jurnal Manajemen dan Ekonomi, 2025)
This research aims to test and analyze partially and simultaneously the influence of company size, leverage and managerial ownership on earnings management in manufacturing companies in the food and beverage sub-sector listed on the BEI for the period 2018 – 2022. The type of research used is quantitative research and empirical approaches. The population in this research is all food and beverage sub-sector manufacturing companies listed on the BEI. Sampling used a purposive sampling technique. The data collection technique in this research uses secondary data. From the results of this test it can be concluded that partially Company Size has no effect and is not significant on Profit Management, Leverage has no effect and is not significant on Profit Management, and Managerial Ownership has no effect and is not significant on Profit Management. Meanwhile, simultaneously Company Size, Leverage and Managerial Ownership have no effect and are not significant on Profit Management in Food and Beverage Sub-Sector Manufacturing Companies listed on the BEI for the 2018 - 2022 period.